IMPLEMENTASI PAJAK BUMI DAN BANGUNAN (PBB) PADA KAWASAN BERIKAT NUSANTARA (KBN) CAKUNG JAKARTA TIMUR UNTUK TIGA PERUSAHAAN PERIODE TAHUN 2013-2015 - Jiwa Pribadi Agustino; Yuliawan Yuliawan; Deris Sandrina (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2016)
Earth including the waters and the natural riches contained therein plays an important role in national development. To realize the national development, in need of awareness of the people to pay taxes. Definition of land and building tax is generally imposed on land and buildings, the tax rate is determined by the state of the object that is the earth / land / buildings. Nusantara Bonded Zone (KBN) Cakung East Jakarta who stood on four hectares of land have the obligation to pay land and building tax (PBB). Method of research done in this final project through library research and field study. The author visited many libraries and uses several methods of data collection by searching the data - the data relating to the company implemntasi tax on land and building (UN) on the archipelago Bonded Zone (KBN) Cakung, East Jakarta. Authors to conclude that the Nusantara Bonded Zone (KBN) Cakung East Jakarta has implemented the obligation to pay tax on land and building under the legislation in force, and the company should maintain consistency in the field of taxation for the future.